Reading the creation narrative in Genesis 1-2:4a against its ancient Near Eastern background - Dyssel, Allan (Stellenbosch : Stellenbosch University, 2007)
Thesis (MPhil (Ancient Studies. Centre for Bible Interpretation and Translation in Africa))--Stellenbosch University, 2007.